Le défi de la transition énergétique en Amazonie brésilienne - Céline Broggio; Marcio Cataia; Martine Droulers; Sébastien Velut (VertigO, 2014)
This article intends to study the energy transition in Brazilian Amazonia, region for a long time isolated, late of development, but with real potentialities. The energy transition is there correlated to the specificities of this territory, in a process of inclusion within the national economy of a Brazil proud of its large proportion of renewable energies which intends to diversify its energy balance. The case of the State of the Pará, in oriental Amazonia, can be considered as "monohydroelectric " oriented. It differs from the case of the State of Amazonas which tends to an energy mix. The energy transition is understood here as a process of development by which a society rapidly growing and expanding, as the Brazilian, resolves its shortages of energy resources taking into consideration climatic impacts; more specifically in Amazonia, where the environmental issue stays in the center of policies of territorial development and in particular as far as the hydroelectric potential is concerned. We try here an approach of those paradoxes.